Schreiben mit der Hand Begriffe - Diskurs - Praktiken - Gredig, Andi (Sprachwissenschaft, 2021)
Why do people still write by hand today? Is typing by hand actually handwriting? And what have signatures got to do with identity? Andi Gredig explores these and many other questions about handwriting from a linguistic and cultural studies perspective. He organizes the complex terminology of writing and script, explores common notions of what handwriting is and can be, and traces current practices of handwriting on the basis of text types such as greeting cards, sketches, and notes. The systematic and precise linguistic analysis of the ideologically contested subject of handwriting reveals some surprising insights. Andi Gredig is a researcher and lecturer at the German Department of the University of Zurich. As a layouter and editor in the linguistics department, he also edits and designs texts in the humanities and deals intensively with typography. In the summer of 2020, he completed his doctorate at the University of Zurich on the topic of handwriting.